Comparing conventional and modified Seldinger techniques using a micro-insertion kit for PICC placement in neonates: a retrospective cohort study - van Rens, Matheus F. P. T.; Hugill, Kevin; van der Lee, Robin; Francia, Airene L. V.; van Loon, Fredericus H. J.; Bayoumi, Mohammad A. A. (Frontiers in Pediatrics, 2024)
Objective: To assess the comparative effectiveness of conventional splitting needle or peelable cannula versus the Modified Seldinger Technique (MST), utilizing a dedicated micro insertion kit, across various clinically significant metrics including insertion success, complications, and catheter-related infections.A retrospective observational cohort study using an anonymized data set spanning three years (2017-2019) in a large tertiary-level neonatal intensive care unit in Qatar.Results: A total of 1445 PICC insertion procedures were included in the analysis, of which 1285 (89%) were successful. The primary indication for insertion was mainly determined by the planned therapy duration, with the saphenous vein being the most frequently selected blood vessel. Patients exposed to MST were generally younger (7±15 days versus 11±26 days) but exhibited similar mean weights and gestational ages. Although not statistically significant, the MST demonstrated slightly higher overall and first-attempt insertion success rates compared to conventional methods (91% versus 88%). However, patients undergoing conventional insertion techniques experienced a greater incidence of catheter-related complications (p<0.001). There were 39 cases of catheter-related bloodstream infections (CLABSI) in the conventional group (3.45/1000 catheter days) and 8 cases in the MST group (1.06/1000 catheter days), with this difference being statistically significant (p<0.001). Throughout the study period, there was a noticeable shift towards the utilization of the MST kit for PICC insertions.The study underscores the viability of MST, facilitated by an all-in-one micro kit for neonatal PICC insertion. Utilized by adept and trained inserters, this approach is associated with improved first-attempt success rates, decreased catheter-related complications, and fewer incidences of CLABSI. However, while these findings are promising, it's imperative to recognize potential confounding factors. Therefore, additional prospective, multicenter studies are recommended to substantiate these results and ascertain the comprehensive benefits of employing the all-in-one kit.